From software architecture models to pipelines: a conceptual framework for model transformation in DevOps - Karlovs-Karlovskis, Uldis; Ņikiforova, Oksana; Pastor, Oscar; Jansone, Anita; Vēveris, Kristijans (Frontiers in Computer Science, 2025)
Since its emergence in 2009, DevOps has significantly advanced software development. Numerous studies have explored the evolution of DevOps and its related methodologies. Some of this research has investigated how model-driven engineering (MDE) can enhance the adoption and implementation of CI/CD practices, commonly known as DevOps pipelines. MDE, originating in the 1980s, offers a distinct approach to software development compared to the traditional “code is the model” mindset. This paper examines the potential synergies between MDE and DevOps, specifically reviewing existing studies on the key artifacts of DevOps pipelines. Our findings indicate that current efforts have not yet sufficiently generalized or formalized reusable transformation rules for a DevOps pipeline model and its corresponding meta-model. These elements are crucial for a successful MDE approach. Therefore, this study proposes an application of the model transformation concept to the DevOps pipeline model. Furthermore, it conceptualizes a reusable model transformation solution capable of generating both the DevOps pipeline model and its resulting code from a software architecture model. The broad research presented here identifies requirements for a potentially groundbreaking future DevOps solution.